Will dispatchability be a main driver to the European Union cooperation mechanisms for concentrated solar power?. Issue 1 (2nd January 2021) - Kiefer, Christoph P.; Caldés, Natalia; Del Río, Pablo
ABSTRACT: The use of the European Union cooperation mechanisms for concentrated solar power (CSP) projects could kill two birds with one stone. First, CSP electricity can cover demand when variable renewables cannot generate. Second, CSP projects deployed under the cooperation mechanisms could contribute to a European-wide optimization of resource use and grid management. This paper analyzes whether the dispatchable nature of CSP is a main driver to the use of the cooperation mechanism for this technology. Based on an expert elicitation and a survey to different types of stakeholders, our results show that, indeed, dispatchability will be the main driver to the use of the cooperation mechanisms for CSP projects in the future. The findings suggest that two types of policy interventions will be required to encourage the use of these mechanisms for CSP. Some policy measures should be directed at the technology itself, whereas other policies should target the cooperation mechanisms.